Casa e caminho no mito de origem Mỹky: por um currículo ética e esteticamente intercultural - Souza, Francisco Josivan de (2008)
This study is about the urgency of an ethical and aesthetically mindful School for the humans who compose it. It s based on the indigenous myth of The Stone Home , of the Mỹky people. In this myth, House and Way appear like archetypes that intertwine themselves with the stillness and the wager, as who s dreaming of Walking from the Home to the hope that will be the construction of the coziness. The desire inside this work is a School that can be a cozy place. In this School, living together with the Other, we wagered in the not-yet dream, that will only be extant, if we leave Home and, from it, start an ethical-aesthetical way of living. The School is the necessary ethos of developing life in its totality; it is the Home from where students gaze at the way and build possible dreams, pro-ject the possible Utopia. Finally, a curriculum that rouse to the delight, then the desire of this Walking will be, itself, Aesthetic. Otherwise, it will not be creative Walking, it will be blunting. Similarly, the aesthetical dimension is, necessarily, an opened Way; it is curriculum. Walking is aesthetically building curriculum. This work´s purpose is to transform curriculum into verb and it is certain that it will be ethos for the tempting action of the human way of being educated and educator